2021
DOI: 10.3390/cancers13225813
|View full text |Cite
|
Sign up to set email alerts
|

UK Women’s Views of the Concepts of Personalised Breast Cancer Risk Assessment and Risk-Stratified Breast Screening: A Qualitative Interview Study

Abstract: Any introduction of risk-stratification within the NHS Breast Screening Programme needs to be considered acceptable by women. We conducted interviews to explore women’s attitudes to personalised risk assessment and risk-stratified breast screening. Twenty-five UK women were purposively sampled by screening experience and socioeconomic background. Interview transcripts were qualitatively analysed using Framework Analysis. Women expressed positive intentions for personal risk assessment and willingness to receiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
124
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(128 citation statements)
references
References 38 publications
4
124
0
Order By: Relevance
“…Our participants' positive acceptance of risk stratification is consistent with findings from previous research in less informed participants that focused on specific cancer types 11–13,24,28–32 . The possibility for risk assessment to support behaviour change has also been made by members of the public previously 24 .…”
Section: Discussionsupporting
confidence: 85%
See 3 more Smart Citations
“…Our participants' positive acceptance of risk stratification is consistent with findings from previous research in less informed participants that focused on specific cancer types 11–13,24,28–32 . The possibility for risk assessment to support behaviour change has also been made by members of the public previously 24 .…”
Section: Discussionsupporting
confidence: 85%
“…Such concerns around accepting reduced screening for those at low risk have been reported previously. 13 , 14 , 28 , 30 , 31 , 32 , 35 Coupled with findings that overdetection in population screening is acceptable to the public and that many are willing to undergo diagnostic testing regardless of cancer risk, 36 , 37 this reinforces the relatively low importance placed by the public on the potential harms of screening people at low risk. We were able to observe that among our participants this was a matter of fairness, with many initially seeking equality in screening (meaning the equal provision of and access to screening services, according to Sasieni's definition) before considering the implications and becoming more favourable to a more equitable risk‐stratified approach (attempting to equalize cancer outcomes).…”
Section: Discussionmentioning
confidence: 74%
See 2 more Smart Citations
“…33 Furthermore, research has shown that women require prompting to consider screening harms in low-risk pathway scenarios, and so, addressing awareness and understanding of the harms is necessary for communicating low-risk pathways to women. 28 Despite heightened concerns from the professional stakeholders that women would not receive the change to low-risk pathways well, women in fact had concerns that were less severe than both the HCPs and NSFs. Women showed that with good communication from professional experts, most worries would be alleviated, and given it is a Government programme, they would be confident in what was advised.…”
Section: What This Study Adds To the Existing Literaturementioning
confidence: 99%